Respuesta :

Answer:

It's in the screenshot hope it helpsss

Step-by-step explanation:

Ver imagen 27eddinsa
Ver imagen 27eddinsa

Answer:

See below

Step-by-step explanation:

y = 2x + 4     Substitute this for y in the second equation

6x - 3y = -12

6x - 3(2x + 4) = - 12  Substitute this for y for 2x + 4

6x - 3(2x) -3(4) = -  12    Distributive property

6x - 6x - 12 =  - 12

(6x - 6x) -12 = - 12   like terms together

 0 - 12 = - 12       Simplify

-12 = -12        True equation so x is equal to any number  and you have the same equation